Learning styles as a tool to effectively support workplace learning in multinational organisations - Ruiz, Erendira (My University, 2018)
The benefits of education are indisputable. After formal education, in our workplace, learning continues. However, perspectives, methodologies and time delivery change from one setting to the other. Most of the time, in our workplace, know-how is transferred as training. The differences in format are basically its length and its learning objectives. Training in the workplace should be more practical and enhance skills and competencies for the trainees in the workplace. The goal of this literature review is to find best practices for the trainer in order to deliver effective training in multinational organisations. Because multinational organisations are formed by multicultural teams, the initial suggestion is that the trainer takes into consideration the different approaches to receive knowledge. Differences might arise due to cultural differences or learning styles.
Keywords: Learning styles; culture; workplace learning; training; trainer; trainee; multinational organisations; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|